Question
upstudy study bank question image url

Find the equation of the circle passing through the point \( (3,4) \) and having equations of two of its diameters \( x+y-14=0 \) and \( 2 x-y-4=0 \quad \) Ans: \( x^{2}+y^{2}-12 x-16 y+75=0 \)

Ask by Lindsey Ryan. in Nepal
Feb 17,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The equation of the circle is \( x^{2} + y^{2} - 12x - 16y + 75 = 0 \).

Solution

To find the equation of the circle that passes through the point \( (3,4) \) and has diameters defined by the lines \( x+y-14=0 \) and \( 2x-y-4=0 \), we can follow these steps: 1. **Find the intersection of the diameters**: The center of the circle will be at the intersection of the two diameters. 2. **Calculate the intersection point**: We will solve the system of equations given by the two lines. 3. **Use the center and the point on the circle to find the radius**: The radius can be calculated as the distance from the center to the point \( (3,4) \). 4. **Formulate the equation of the circle**: Using the center and radius, we can write the equation of the circle. ### Step 1: Find the intersection of the diameters We have the equations: 1. \( x + y - 14 = 0 \) (Equation 1) 2. \( 2x - y - 4 = 0 \) (Equation 2) Let's solve these equations simultaneously. ### Step 2: Solve the system of equations From Equation 1, we can express \( y \) in terms of \( x \): \[ y = 14 - x \] Now, substitute \( y \) into Equation 2: \[ 2x - (14 - x) - 4 = 0 \] \[ 2x - 14 + x - 4 = 0 \] \[ 3x - 18 = 0 \] \[ x = 6 \] Now substitute \( x = 6 \) back into the expression for \( y \): \[ y = 14 - 6 = 8 \] Thus, the center of the circle is at the point \( (6, 8) \). ### Step 3: Calculate the radius Now we need to find the radius, which is the distance from the center \( (6, 8) \) to the point \( (3, 4) \): \[ r = \sqrt{(6 - 3)^2 + (8 - 4)^2} \] \[ r = \sqrt{3^2 + 4^2} = \sqrt{9 + 16} = \sqrt{25} = 5 \] ### Step 4: Formulate the equation of the circle The general equation of a circle with center \( (h, k) \) and radius \( r \) is given by: \[ (x - h)^2 + (y - k)^2 = r^2 \] Substituting \( h = 6 \), \( k = 8 \), and \( r = 5 \): \[ (x - 6)^2 + (y - 8)^2 = 5^2 \] \[ (x - 6)^2 + (y - 8)^2 = 25 \] Expanding this equation: \[ (x^2 - 12x + 36) + (y^2 - 16y + 64) = 25 \] \[ x^2 + y^2 - 12x - 16y + 100 = 25 \] \[ x^2 + y^2 - 12x - 16y + 75 = 0 \] Thus, the equation of the circle is: \[ \boxed{x^2 + y^2 - 12x - 16y + 75 = 0} \]

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

Sure! Here's some additional knowledge for you: Did you know that the equations of the diameters help us find the center of the circle? The intersection of these diameters gives the center. By solving the simultaneous equations \( x + y = 14 \) and \( 2x - y = 4 \), you can easily find the center, which turns out to be \( (8, 6) \). Once you have the center, calculating the radius is just as fun! You can use the distance formula to find the distance from the center to the point \( (3,4) \). Plugging those values into the distance formula gives you the radius. Then you'll use the standard formula for a circle to find the final equation. It's like piecing together a little puzzle!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy